2017
DOI: 10.1016/j.polymer.2017.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropenone-masked dibenzocyclooctyne end-functionalized polymers from reversible addition-fragmentation chain transfer polymerization

Abstract: Functional reversible addition-fragmentation chain transfer polymerization (RAFT) agent was developed to have a cyclopropenone-masked dibenzocyclooctyne end group. RAFT polymerization was then explored on three typical types of vinyl monomers in free radical polymerization such as styrene, methyl methacrylate, and tert-butyl acrylate. The living polymerization behaviors were demonstrated for all three cases, which guaranteed the production of well-defined polystyrene, poly(methyl methacrylate), and poly(tert-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It should be noted that the minor peak distribution in GPC traces of FSB‐PNIPAAm‐PEG was contributed to the excessively unreacted TBDMS‐PEG building block. This similar phenomenon was observed in a previous study . Most importantly the molecular weight at this elution volume is estimated as 32 000 g mol −1 , approximately equal to the sum of the FSB‐PNIPAAm and PEG‐OH molecular weights, indicating the successful formation of the FSB‐PNIPAAm‐PEG diblock copolymer by the SuFEx click reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the minor peak distribution in GPC traces of FSB‐PNIPAAm‐PEG was contributed to the excessively unreacted TBDMS‐PEG building block. This similar phenomenon was observed in a previous study . Most importantly the molecular weight at this elution volume is estimated as 32 000 g mol −1 , approximately equal to the sum of the FSB‐PNIPAAm and PEG‐OH molecular weights, indicating the successful formation of the FSB‐PNIPAAm‐PEG diblock copolymer by the SuFEx click reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We also checked the solvent effect with eleven different organic solvents (See Table S7) and further confirmed that toluene or chlorobenzene was best choice for this reaction. In addition, lower temperature was beneficial to the achieving of higher enantioselectivity (entries [14][15][16]. Notably, the evaluation of nickel catalysis was not effective in this reaction (Entry 17), which supported the privileged role of Pd/L15 catalyst system in this enantioselective (3+2) spiroannulation process.…”
Section: To Avoid Decarbonylation During C-c Bond Activation To Increase the Nucleophilicity Of The Active Intermediatesmentioning
confidence: 92%
“…In addition, carbon-carbon bond activation of small rings for the synthesis and functionalization of cyclic compounds is intrinsically challenging to a variety of synthetic chemistry and pharmaceutical application. Among the small rings, cyclopropenones, a privileged type of small and strained ring compounds bearing two functional groups as ketone and olefin, have drawn increasing attentions because of their ability in the versatile reactivity for the construction of functional polymers, [12][13][14][15][16][17] fluorogenic probes, 18,19 natural products or biologically useful molecules in medicinal chemistry, [20][21][22][23][24] and as organocatalysts. [25][26][27][28][29] Since the pioneering synthesis by Breslow in 1959, 30,31 cyclopropenones have often been developed as valuable building blocks for the synthesis of complex molecules, and they are notable for their amphiphilic properties as both electrophiles and nucleophiles, and other unusual properties (Figure 1), including high basicity, light-responsive properties, large dipole moments, aromatic characters, and significant angle strain.…”
Section: Introductionmentioning
confidence: 99%
“…Using a strained cyclooctyne initiator for ATRP, Zhang and co‐workers found that polymerization with acrylate monomers did not preserve the strained cyclooctyne [103] . To protect the strained cyclooctyne during polymerization, they reported that ATRP and RAFT with a cyclopropenone‐masked dibenzocyclooctyne prevented side reactions [104, 105] . After polymerization, UV light unmasked the cyclooctyne and could be used to prepare T‐ or H‐shaped block copolymers (Figure 16 b).…”
Section: Polymer Crosslinking and Architecturesmentioning
confidence: 99%
“…[103] To protect the strained cyclooctyne during polymerization, they reported that ATRP and RAFT with ac yclopropenone-masked dibenzocyclooctyne prevented side reactions. [104,105] After polymerization, UV light unmasked the cyclooctyne and could be used to prepare T-or H-shapedb lock copolymers (Figure 16 b). Meanwhile,B arz and co-workerss ynthesized block copolypeptides, polypeptoids, and block copolypept(o)ides and found that SPAAC chemistry was more effective forc oupling than CuAACo rn ative chemical ligation.…”
Section: Polymer Crosslinking and Architecturesmentioning
confidence: 99%